2005
DOI: 10.1079/asc41380305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restricted feeding and re-feeding of Barbarine lambs: intake, growth and non-carcass components

Abstract: Link to this article: http://journals.cambridge.org/abstract_S1357729805000846How to cite this article: M. Mahouachi and N. Atti (2005). Effects of restricted feeding and re-feeding of Barbarine lambs: intake, growth and noncarcass components. AbstractFifty intact male Barbarine lambs were used to assess the effects of restricted feeding and re-alimentation on intake, growth and non-carcass components. Five lambs were slaughtered at the start of the trial, the remainder were randomly allocated into three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
(34 reference statements)
6
19
0
1
Order By: Relevance
“…This higher gain could not be attributed to DMI because intake values were not different between realimented (RR) and control groups, but possibly due to the better FG in realimented lambs and/or the decreased heat production during the restriction and its continuation during realimentation (Yambayamba et al, 1996). These results are in agreement with those of Mahouachi and Atti (2005), but not with those of Homem Junior et al (2007), who reported that rapid gain during realimentation was associated with increased feed intake. The apparent inconsistency may be explained by the differences in levels of restriction and realimentation, composition of diets, age of animal, and periods of restriction and realimentation (Tolla et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This higher gain could not be attributed to DMI because intake values were not different between realimented (RR) and control groups, but possibly due to the better FG in realimented lambs and/or the decreased heat production during the restriction and its continuation during realimentation (Yambayamba et al, 1996). These results are in agreement with those of Mahouachi and Atti (2005), but not with those of Homem Junior et al (2007), who reported that rapid gain during realimentation was associated with increased feed intake. The apparent inconsistency may be explained by the differences in levels of restriction and realimentation, composition of diets, age of animal, and periods of restriction and realimentation (Tolla et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Also, it has been shown that moderate feed restriction resulted in appreciable changes in the metabolism of the liver tissue (Tovar-Luna et al, 2007). In other reports, liver weight was not affected by a period of feed restriction followed by realimentation (Mahouachi and Atti, 2005;Shadnoush et al, 2011;Abouheif et al, 2013). The high growth rate for liver tissue exhibited by compensatory-grown lambs probably reflects hypertrophy of the liver tissue upon realimentation after a period of growth restriction (Sami et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations